Analisis Kualitas Rokok di Toko Madura Klampis Ngasem dari Segi Logistik dengan Metode DMAIC. - Sulton, Ali; Aditya, Dwi Julian; Azeryan, Vitho; Yuliawati, Evi (Prosiding Seminar Nasional Sains dan Teknologi Terapan, 2024)
This study employs the DMAIC approach to address the issue of torn cigarette defects at Toko Madura. The Define, Measure, Analyze, Improve, and Control steps are used to identify, analyze causes, and design effective improvement solutions. The Define step specifically identifies the existing problem, which is torn cigarette defects. The Measure step involves collecting data related to the number and location of torn defects. The Analyze step is used to determine the causes of the torn defects, which may originate from the production process, inventory management, or product handling. The Improve step is designed to implement effective corrective solutions, while the Control step is applied to ensure the implemented solutions are sustainable and can reduce or eliminate torn cigarette defects at Toko Madura. The goal is to enhance the quality of cigarette products and optimize customer satisfaction at Toko Madura Klampis Ngasem.